PENERAPAN EDUKASI KEAMANAN PANGAN UNTUK MENINGKATKAN KUALITAS PENJAMAH MAKANAN DI INSTALASI GIZI - Setyaningrum, Yahmi Ira; Ambarsari, Elisa; Widya, Ariesta (Mediasi: Jurnal Pengabdian Masyarakat, 2025)
Food safety is a crucial aspect in food service, particularly in hospital nutrition installations or other healthcare institutions. Food handlers play a vital role in maintaining the quality and safety of the food served. This study aims to evaluate the effectiveness of food safety education in improving the knowledge, attitudes, and practices of food handlers in the nutrition installation. A quantitative approach was used with a pre-experimental design (one group pretest-posttest). The education was delivered through interactive training covering the Five Keys to Safer Food. The results showed a significant increase only in knowledge scores by 22%, while there were no significant changes in the attitudes and practices of the food handlers after the education. These findings indicate that food safety education is effective in improving the knowledge of food handlers, which ultimately contributes to enhancing the quality of nutrition services. It is recommended that educational programs be conducted continuously and become an integral part of nutrition installation management.